Aloha [videorecording (DVD)] - Crowe, Cameron, 1957-; Cooper, Bradley; McAdams, Rachel, 1978-; Stone, Emma, 1988-; Murray, Bill, 1950 September 21-; Baldwin, Alec, 1958-; Krasinski, John, 1979- (Sony Pictures Home Entertainment, 2015)
A celebrated military contractor returns to the site of his greatest career triumphs, the US Space program in Honolulu, Hawaii, and reconnects with a long-ago love while unexpectedly falling for the hard-charging Air Force watchdog assigned to him.